The General Path Of Trends In Dust Phenomena And Their Relationship To Climatic Elements In Najaf Station For The Period (1975-2017) - Kadham Alkinani, Nahad Khudhair; Sami Mohammed, Ruqaya (Opción, 2019)
The research deals with analyzing the general course of trends in dust phenomena and their relationship to climatic elements in the Najaf climatic sta- tion. The study focused on finding the general trend of dust phenomena repre- sented by dust storms, ascending dust, and suspended dust during the months of the year in addition to the annual total for each phenomenon and find the correlation between these dust phenomena and climatic elements, such as temperature, atmospheric pressure, wind speed, relative humidity, falling rain and evaporation, and to determine which of these relations are soft or inverse, or the relationship between them may not exist. The research aims to determine the general direction of dust phenomena in the Najaf climatic station and find the relationship between those phenomena and climatic ele- ments through studying monthly and yearly rates, and determining the type of relationship between dust phenomena and climatic elements. The research reached several results, the most important of which are: 1- That the general trend of dust storms was to decrease during the months (January, February, July, August, September, December) while dust storms tended to rise during the months (March, April, May, June, October As for the annual total of dust storms, it is heading upward to reach (0.04). The general trend of bullish dust was downward during all months, and the annual total of bullish dust is head- ing downward to (-0.96). The general trend of trapped dust was upward dur- ing all months, while the annual total of trapped dust was heading upward to reach (2.22). 2- he relationship between dust storms and climatic elements is very weak or not all. The correlation between ascending dust, tempera- ture, wind speed, and evaporation is a direct correlation, while the correla- tion between ascending dust, atmospheric pressure, relative humidity and falling rain is an inverse relationship. The relationship between suspended dust, temperature, wind speed, and evaporation is a direct relationship. The relationship between suspended dust, atmospheric pressure, relative humidity, and precipitation is inverse.